2007
DOI: 10.1111/j.1442-200x.2007.02417.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolated adrenocorticotropic hormone deficiency presenting with psychomotor retardation

Abstract: Isolated adrenocorticotropic hormone defi ciency (IAD) is a rare pituitary disease in childhood and is considered to be a differential diagnosis in cases of ketotic hypoglycemia. 1 Although a few patients have an infl ammation or organic lesion in the pituitary gland, the etiology of this disorder has remained unclear in the majority of cases. Adrenocorticotropic hormone (ACTH) is produced from the ACTH precursor, proopiomelanocortin (POMC), by prohormone convertase 1 (PC1), and POMC gene expression requires a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(25 reference statements)
1
2
0
Order By: Relevance
“…In addition, a transient form of IAD has been described in patients after traumatic brain injury (TBI) 19 . Neurological manifestations of IAD -which were observed in our patient -have also been described, and patients have been reported presenting with delirium 20 , involuntary movements 21 , and psychomotor retardation 22 . However, to our knowledge, this is the first reported case of a patient with isolated ACTH deficiency presenting outside of the newborn period with new-onset seizure activity.…”
Section: Discussionsupporting
confidence: 77%
“…In addition, a transient form of IAD has been described in patients after traumatic brain injury (TBI) 19 . Neurological manifestations of IAD -which were observed in our patient -have also been described, and patients have been reported presenting with delirium 20 , involuntary movements 21 , and psychomotor retardation 22 . However, to our knowledge, this is the first reported case of a patient with isolated ACTH deficiency presenting outside of the newborn period with new-onset seizure activity.…”
Section: Discussionsupporting
confidence: 77%
“…Almost all patients had had difficulty at school that disappeared once they began their Hydrocortisone® replacement therapy. Nozue et al [4] reported the case of a patient with isolated ACTH deficiency and psychomotor retardation, suggesting the specific role of the hypoglycemia and/or low blood pressure. Shulman et al [11] also reported symptoms that may mimic gastrointestinal illness or a psychiatric disorder, particularly behaviour changes or depression.…”
Section: Discussionmentioning
confidence: 99%
“…Metherell et al [3] reported 7 cases, 4 of whom were less than one year old, with two different mutations in 2 of them, and 3 of whom were over 5 years old. Nozue et al [4] reported one Japanese case and collected 7 more cases, they included 3 early onset and 5 late onset forms. Mutations in the TPIT gene are associated only with the early onset form [2] .…”
Section: Introductionmentioning
confidence: 99%